Electrochemical treatment of 2, 4–dichlorophenol using a nanostructured 3D–porous Ti/Sb–SnO2–Gr anode: Reaction kinetics, mechanism, and continuous operation. (October 2017) - Asim, Sumreen; Zhu, Yunqing; Batool, Aisha; Hailili, Reshalaiti; Luo, Jianmin; Wang, Yuanhao; Wang, Chuanyi
Abstract: 2, 4–dichlorophenol (2, 4–DCP) is considered to be a highly toxic, mutagenic, and possibly carcinogenic pollutant. This study is focused on the electrochemical oxidation of 2, 4–DCP on nanostructured 3D–porous Ti/Sb–SnO2 –Gr anodes, with the aim of presenting a comprehensive elucidation of mineralization process through the investigation of influential kinetics, the reactivity of hydroxyl radical's and analysis of intermediates. High efficiency was achieved at pH of 3 using Na2 SO4 electrolytes at a current density of 30 mA cm −2 . Under the optimized conditions, a maximum removal of 2, 4–DCP of up to 99.9% was reached, whereas a TOC removal of 81% was recorded with the lowest ECTOC (0.49 kW h g −1 ) within 40 min of electrolysis. To explore the stability of the 3D–Ti/Sb–SnO2 –Gr electrodes, a continuous electrochemical operation was established, and the consistent mineralization results indicated the effectiveness of the 3D–Ti/Sb–SnO2 –Gr system concerning its durability and practical utilization. EPR studies demonstrated the abundant generation of OH radicals on 3D–Ti/Sb–SnO2 –Gr, resulting in fast recalcitrant pollutant incineration. From dechlorination and the reactivity of the OH radicals, several intermediates including six cyclic byproducts and three aliphatic carboxylic acids were detected, and two possible degradation pathways were proposed that justify the complete mineralization of 2, 4–DCP. Graphical abstract: Highlights: Electrochemical treatment of 2, 4–DCP on 3D–porous Ti/Sb–SnO2 –Gr anodes. EPR evaluation to figure out the effect of .OH radicals on degradation rate. Electrodes stability investigation in continuous operation for practical utilization. High mineralization of 2, 4–DCP at low energy cost. Reaction mechanism demonstration based on the organic and inorganic byproducts.